Canopy nutrient content of a Quercus ilex L. forest: fertilization and irrigation effects - SABATE, Santiago; Gracia, Carlos a; Ecology, Forest; Barcelona, Universitat De (Forest Ecology and Management, 1994)
A multifactorial ANOVA experiment was designed for a Quercus ilex L. forest at the Prades Experimental Complex of Catchments in Tarragona (northeast Spain). The purpose of this study was to clarify the relative importance of water, nitrogen and phosphorus as factors controlling primary production. Eight plots comprising all possible combinations of the three factors (including a control) were laid out in three replicate blocks. Fertilizers were applied in March 1989 (125 kg ha−1 P, 250 kg ha−1 N). Irrigation was applied at a rate of 20 mm week−1 during the warm season. Nitrogen and phosphorus contents and their distribution in leaves and stems as a response to the experiment are presented in this paper. These variables as well as the structural characteristics were selected because they are among the most dynamic and should present changes over short time periods following changes in environmental conditions. The values before initial treatments (autumn 1988) and after treatments (summer 1990) were analysed. Results showed that water treatments affect the nutrient content; the lower concentrations found in water treatments may probably be explained as a dilution effect after an increase of production. Nitrogen treatments significantly increase the nitrogen concentration in young leaves while phosphorus treatments do not have significant effect on the phosphorus concentrations. Nevertheless, phosphorus treatment significantly lowers the potassium concentration.
Keywords: Canopy; fertilization; irrigation; nutrient content; Quercus ilex